F. DOSTOEVSKY IN THE LATEST WORKS OF K. STEPANYAN - GEVORGYAN, TATYANA (Bulletin of Yerevan University H: Russian Philology, 2021)
This article is dedicated to the memory of Karen Stepanyan (1952-2018), a prominent expert in literary studies, internationally known in particular for his numerous scientific works and extensive organizational activity in the field of studies about Dostoevsky. The author presents in general terms the activity of Karen Stepanyan in the sphere of literary criticism and science, then examines latest published works of the scientist in details, in the context of their connection with his new scientific concept, which remained unfinished.